2006
DOI: 10.1136/bjo.2006.102624
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of cornea pseudoguttata

Abstract: Aim: To report on cornea pseudoguttata which occurred in 44 eyes from 40 patients. Methods: In 3521 consecutive patients seen at a local eye clinic, eyes were examined with a slit-lamp biomicroscope in specular illumination. When guttate appearance was found, specular microscopy was performed. Results: Cornea pseudoguttata was found in 44 eyes of 40 patients (1.1%). All patients had some form of anterior-segment ocular diseases, including keratitis (corneal infiltration) with contact lens wear (n = 16), epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Cornea pseudoguttata, thought to correspond to patchy transient corneal endothelial edema, 20,21 was observed during an acute attack, but all patients had normal endothelium by biomicroscopy between attacks. The features of acute keratoendotheliitis on day 1 are presented for Patient 4-01, a sporadic case.…”
Section: Resultsmentioning
confidence: 99%
“…Cornea pseudoguttata, thought to correspond to patchy transient corneal endothelial edema, 20,21 was observed during an acute attack, but all patients had normal endothelium by biomicroscopy between attacks. The features of acute keratoendotheliitis on day 1 are presented for Patient 4-01, a sporadic case.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the follow‐up of some cases with pseudo‐guttata, even if confluent, it has been concluded that they can resolve without obvious damage to the corneal endothelium 19 . Further studies would appear to be warranted and would be useful to assess the progressive (or resolving) effects of non‐dystrophic guttata on central corneal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The low‐magnification prints from the specular microscope were examined and assigned a grade 19 of 1 (‘several dark spots’), 2 (many dark spots not in contact with each other) or 3 (numerous dark spots that are in contact with each other). The last can also be referred to as semi‐confluent or confluent guttata.…”
Section: Methodsmentioning
confidence: 99%
“…Nakashima et al 16 reported the presence of corneal pseudoguttata in 44 out of 3,521 patients presenting consecutively to a local eye clinic. Of these patients, 16 were suffering from contact lens-induced keratitis.…”
Section: Differential Diagnosismentioning
confidence: 98%